Panax Notoginseng Saponins Protect Cardiac Myocytes Against Endoplasmic Reticulum Stress and Associated Apoptosis Through Mediation of Intracellular Calcium Homeostasis - Chen, Jun; Xue, Rui; Li, Li; Xiao, Li Li; Shangguan, Jiahong; Zhang, Wenjing; Bai, Xueyang; Liu, Gangqiong; Li, Ling (Frontiers in Pharmacology, 2019)
Endoplasmic reticulum (ER) stress has been demonstrated to play important roles in the pathogenesis of various cardiovascular diseases. ER stress pathway is therefore a promising therapeutic target in cardiovascular disease. Although panax notoginseng saponins (PNS) is one of the patent medicines, which are traditionally used as the treatment for cardiovascular disorders, its effects on ER stress remains unexploited so far. This study investigates the effects of PNS on ER stress and its associated cell apoptosis along with the related mechanism. PNS compounds were identified via high performance liquid chromatograph (HPLC) assay. PNS pretreated H9c2 and HL-1 cells were stimulated with thapsigargin (TG) to induce ER stress response and apoptosis. ER stress response was tested by immunofluorescence or immunoblot of the ER protein chaperones – calnexin, BiP and CHOP. Cell viability was tested by methyl thiazolyl tetrazolium (MTT) assay. Cell apoptosis was detected by immunoblot of cleaved caspase-3 and flow cytometry analysis of Annexin V/Propidium Iodide (PI) staining. Cytosolic, mitochondrial and ER calcium dynamics were investigated by calcium imaging. Moreover, ryanodine receptor type-2 (RyR2) overexpression stable cell line was generated to verify the mechanism of RyR2 involved in PNS on the inhibition of ER stress and cell apoptosis. We demonstrate here that PNS protected cardiac myocytes from ER stress response and associated cell death in a concentration-dependent manner. Importantly, PNS reduced the elevation of cytosolic calcium, mitochondria calcium as well as ER calcium in response to either TG or histamine treatment. PNS protection of ER stress was regulated by RyR2 expression. In summary, PNS protection against TG-induced ER stress response and its associated cell apoptosis is calcium dependent. Through the regulation of ER calcium release medicated by RyR2, a novel mechanism for PNS in the prevention of cardiovascular diseases is thereby identified.